A Thematic Review of Preservice Teacher Education Research in Turkey and Reflections of Teacher Education Policies - Yucel-Toy, Banu (TURKISH EDUCATION ASSOC, 2015)
Purpose of this study is to examine trends in preservice teacher education research in Turkey in terms of topic, purpose and method through thematic content analysis and to evaluate the trends in terms of teacher education policies. To this end, 479 articles related to preservice teacher education and published in three rooted journals since 1970 were examined. According to the results, nine themes were extracted and the most widely studied topics were identified as: subject and pedagogical knowledge and attitudes of teacher candidates, evaluation of teacher education program or its components, effects of instructional methods/approaches, information and communication technologies in teacher education and teacher education institutions. Quantitative paradigm is still dominant but an increase in qualitative and mixed studies has been observed since 2000. In terms of policies, problems expressed in the studies prior to 1997 were the issues leading to the 1997 restructuring reform. From this point of view, it can be inferred that these studies might have fed the 1997 reform. On the other hand, after 1997, the studies examined the results and effects of the 1997 restructuring and the 2006 revision reforms; for this reason, it is implied that the policies might have given direction to the studies conducted in this period of time.
Keywords: Preservice teacher education; Research; Content analysis; Method; Teacher education policies; SCIENCE PROCESS SKILLS; MATHEMATICS; KNOWLEDGE; EXPERIENCES; CURRICULUM; STUDENTS; TRENDS; SUPERVISION; INSTRUCTION; PERSPECTIVE; Education & Educational Research